The Formin mDia1 Regulates Acute Lymphoblastic Leukemia Engraftment, Migration, and Progression in vivo - Thompson, Scott B.; Wigton, Eric J.; Krovi, Sai Harsha; Chung, Jeffrey W.; Long, Robert A.; Jacobelli, Jordan (Frontiers in Oncology, 2018)
Leukemias typically arise in the bone marrow and then spread to the blood and into other tissues. To disseminate into tissues, leukemia cells migrate into the blood stream and then exit the circulation by migrating across vascular endothelial barriers. Formin proteins regulate cytoskeletal remodeling and cell migration of normal and malignant cells. The Formin mDia1 is highly expressed in transformed lymphocytes and regulates lymphocyte migration. However, the role of mDia1 in regulating leukemia progression in vivo is unknown. Here, we investigated how mDia1 mediates the ability of leukemia cells to migrate and disseminate in vivo. For these studies, we used a mouse model of Bcr-Abl pre-B cell acute lymphoblastic leukemia. Our data showed that mDia1-deficient leukemia cells have reduced chemotaxis and ability to complete transendothelial migration in vitro. In vivo, mDia1 deficiency reduced the ability of leukemia cells to engraft in recipient mice. Furthermore, leukemia dissemination to various tissues and leukemia progression were inhibited by mDia1 depletion. Finally, mDia1 depletion in leukemia cells resulted in prolonged survival of recipient mice in a leukemia transfer model. Overall, our data show that the Formin mDia1 mediates leukemia cell migration, and drives leukemia engraftment and progression in vivo, suggesting that targeting mDia1 could provide a new method for treatment of leukemia.